Perhitungan Stage Mixer Settler untuk Pemurnian Torium (Th) dari Pelarutan Monasit - Nuri, Hafni Lissa; Prayitno Prayitno; Jami, Abdul (EKSPLORIUM, 2018)
Monazite (Ce, La, Nd, Th)PO4 with thorium (Th) content between 3-4 % is significant enough to be processed to produce Th. The initial treatments conducted by using carbonate base reagents (Na2CO3) for monazite leaching to fetch the uranium. The remaining tailings were dissolved with sulfuric acid to produce Th(SO4)2 solution which is then purified from its impurities. The processing is carried out continuously using a mixer settler with the process steps include Th extraction, Th stripping, and organic solvents regeneration. Thorium extraction uses a primene JM-T (RNH2) organic solvent which is a mixture of 0.15M Primene JM; 5% Tridecanol and 95% Kerosine. Meanwhile, the Th stripping process uses 2M HCl solution. For efficiency, regeneration of organic solvents uses 1% H2SO4. To obtain a high recovery and purity from Th, it is necessary to calculate the number of stage mixer settlers using the McCabe Thiele method. Based on the calculation, the number of stage for extraction process, Th stripping, and organic solvents regeneration are 3, 3, and 2 respectively. The total recovery of Th is obtained at 84.90 % where product purity reaches 99.02 %